Avaliação de diferentes tratamentos de superfície na resistência de união de cerâmica de di-silicato de lítio - Feitosa, Fernanda Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to evaluate the bond strength afforded by different surface treatments on IPS e.max Press ceramic united to Variolink II (both Ivoclar-Vivadent, Liechtenstein), when subjected to tensile test. 330 ceramic bases were divided into 11 groups in accordance with the surface treatment performed: C - control group J - aluminum oxide sandblast, JAraluminum oxide sandblast and silane hot air dry, GEr - surface coating with graphite and treatment with Er: YAG laser (200 mJ of energy intensity and frequency 10 Hz), GErAr - surface coating with graphite, treatment with Er: YAG laser (200 mJ of energy intensity and 10 Hz frequency) and silane hot air dry; Er - treatment with Er: YAG laser (200 mJ of energy intensity and frequency 10 Hz) ErAr - treatment with Er: YAG laser (200 mJ intensity energy and 10 Hz frequency) and silane hot air dry; GNd - coating the surface with graphite and treatment with Nd: YAG laser (120 mJ of energy and intensity of frequency 15 Hz); GNdAr - coating the surface with graphite , treatment with Nd: YAG laser (120 mJ of energy intensity and 15 Hz frequency) and silane hot air dry; Nd - treatment with Nd: YAG laser (120 mJ of energy intensity and frequency 15 Hz); NdAr - treatment with Nd: YAG laser (120 mJ of energy and intensity of frequency 15 Hz) and silane hot air dry. The resin cement that unite the specimens was cured for 40 seconds using the LED cure equipment (Radii-cal SDI). Then they were termomechanical cycled (60N, 1,000 thermical cycles and 24000 mechanical) and were submitted to the tensile test in a universal testing machine EMIC-2000. Data were tested for Dunnet ( α = 5 % ) and 3 ANOVA Way . The Er group showed higher tensile strength greater than the control group and the other groups, while the NdG group presented results of bond strength lower than the control group and the other surface treatments. The other groups did...

O objetivo deste estudo foi avaliar o efeito de diferentes tratamentos de superfície na resistência de união entre a cerâmica de di-silicato de lítio IPS e.max Press (IvoclarVivadent, Liechtenstein) e o cimento resinoso Variolink II (Ivoclar Vivadent, Liechtenstein) quando submetidos a teste de tração. Para isso 330 bases tronco-cônicas de cerâmica de di-silicato de lítio foram aleatoriamente divididas em 11 grupos de acordo com o tratamento a ser realizado: C - grupo controle; J - Jateamento com óxido de alumínio (50 μm); JAr - Jateamento com óxido de alumínio (30 μm) e secagem do silano com ar quente; GEr - Revestimento da superfície com grafite e tratamento com laser Er:YAG(200 mJ de intensidade de energia e 10 Hz de frequência); GErAr – Revestimento da superfície com grafite, tratamento com laser Er:YAG (200 mJ de intensidade de energia e 10 Hz de frequência) e secagem do silano com ar quente; Er - Tratamento com laser Er:YAG (200 mJ de intensidade de energia e 10 Hz de freqüência); ErAr - Tratamento com laser Er:YAG (200 mJ de intensidade de energia e 10 Hz de frequência) e secagem do silano com ar quente; GNd – revestimento da superfície com grafite e tratamento com laser Nd:YAG (120 mJ de intensidade de energia e 15 Hz de frequência); GNdAr – Revestimento da superfície com grafite, tratamento com laser Nd:YAG (120 mJ de intensidade de energia e 15 Hz de frequência) e secagem do silano com ar quente; Nd – Tratamento com laser Nd:YAG (120 mJ de intensidade de energia e 15 Hz de frequência); NdAr – Tratamento com laser Nd:YAG (120 mJ de intensidade de energia e 15 Hz de frequência) e secagem do silano com ar quente. O cimento resinoso que uniu os espécimes foi fotoativado por 40 segundos utilizando o aparelho LED (Radii cal-SDI). Então, foi realizada a ciclagem termomecânica com carga de 60N, 1.000 ciclos termicos e 24000 mecânicos e o ensaio ...
Keywords: Ceramica; Cimentos dentarios; Lasers